O futuro da anatomia : descrição da anatomia clínica, radiográfica, tomográfica e tridimensional de Rupornis magnirostris - Lima, Luiz Felipe Souza de (2020)
Birds of prey play an important role in the balance of several biomes, but their proximity to urban areas often causes harm to the animal. The investigation of clinical surgical approaches requires a precise understanding of the anatomical system, especially when applied to imaging exams of wild animals. In this article we present the clinical anatomy of the long bones of Rupornis magnirostris, roadside hawk, focusing on its express form in the imaging tests adopted. Cadavers were submitted to digital radiography and computed tomography, providing models both two-dimensional imagens and threedimensional images of long bones through the segmentation os tomographic images, both 3D and 2D data were contrasted used in the literature of the long bones of birds perceived in the imaging examinations. The approach presented here provides considerable advantages for the interpretation and communication of anatomical information and its visualization; (2) the 3D model produced from the segmentation process as an interactive model in the form of an embedded 3D image, which can be viewed at any angle and size, allowing the structure to be evidenced as necessary to provide as understanding of the normal anatomy of long bones of this species.